How the estimates of home range size and composition are affected by diurnal, nocturnal and 24-hour sampling methods: example of the red deer (Cervus elaphus) in Slovenia - Jerina, Klemen (Zbornik gozdarstva in lesarstva, 2009)
Most of the previous research on the mammals' home range (HR) is based on diurnal sampling, while the results are often implicitly considered as representative for an entire 24-h period. However, there is a growing body of research on populations, whose habitat selection changes circadianly, which leads to the hypothesis that HR patterns may vary at different periods of the day. This study used 24-h data from 15 red deer equipped with GPS collars to explore differences in the size and composition of their HRs, estimated on diurnal, nocturnal and 24-h samplings. The differences in composition were shown on the forest/non-forest variable. We established that nocturnal, and inparticular the 24-h HRs, largely overlapped with the diurnal HRs (64% and 76%, respectively) and that parts of the HRs that are used exclusively nocturnally are contiguous or adjacent to diurnal HRs. The differences in HR sizes were significant only between diurnal and 24-h HRs. However, the HR composition varied substantially: the average proportion of non-forest areas was 15% in diurnal, 26% in 24-h and 31% in nocturnal HRs. This study demonstrated that with diurnal sampling it is impossible to assess accurately the size and composition of 24-h HRs of red deer in Slovenia. There are several indices that the same is true of several other populations/species. It is therefore important to be aware that HR patterns estimated on the basis of diurnal sampling may be incomplete or even wrong if generalised across the 24-h period.
Keywords: Cervus elaphus; jelenjad; prevalence; razširjenost; Slovenia; Slovenija; telemetrija